Investigating Gender-based Responses in Social Psychology Experiments - Ardita Todri; Petraq Papajorgji; Howard Moskowitz (Journal of cognitive science, 2024)
This paper presents a meta-analysis of 29 studies run using the Mind Genomics approach to quantify how respondents react to messaging and how their reaction impacts decision-making in social psychology experimental research areas. The Mind Genomics studies used were performed during the 2020-2022 period in the USA, Italy, Spain, Albania, and other countries of the Mediterranean basin. The paper focuses on identifying gender differences in response time and evaluations of messages on different topics calculated by the Mind Genomics-Artificial Intelligence system. Further, the meta-analysis results are based on Kahneman's (2011) study results. The study`s general result demonstrates that male and female participants' thinking is intuitive, automatic, and emotionally oriented. The study also confirms that the gender's response time does not affect the results of the experiment. In addition, is argued that gender-based perceptions differ according to the topic and are considered relevant in decision-making on some topics. These study results can be used to predict the experiment's results for new participants without having them repeat the entire experimental procedure. KCI Citation Count: 0